Applied developmental science an advanced textbook - Lerner, Richard M.; Jacobs, Francine Helene; Wertlieb, Donald; Sage eBooks (Thousand Oaks, [Calif.] ; London : SAGE, 2005)
A course textbook adapted from the 4 volume 'Handbook of Applied Developmental Science', this work brings together the latest in theory & application from applied developmental science & the positive psychology movement for students going on to careers working with youth & their families.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Child development; Adolescence; Electronic books